2011
DOI: 10.4028/www.scientific.net/amr.343-344.322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Limestone Powders on Compressive Strength and Setting Time of Portland-Limestone Cement Pastes

Abstract: In this study limestone powders with different particle sizes of 5, 10 and 20 μm were used to replace a part of Portland cement in different replacement levels to produce Portland-limestone cement pastes. The percentages of limestone replacement are 0, 5, 7.5, 10, 12.5, 15 and 20% by weight. The effect of fineness and the amount of limestone powders on compressive strength and setting time are investigated. It has been established that limestone replacement causes reduce the compressive strength due to the dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 8 publications
3
14
0
1
Order By: Relevance
“…3. A similar effect was observed by Thongsanitgarn et al [24] on incorporating fine limestone in the cement paste.…”
Section: Fig2 Effect Of Waste Addition On Water Of Consistency Of Csupporting
confidence: 83%
“…3. A similar effect was observed by Thongsanitgarn et al [24] on incorporating fine limestone in the cement paste.…”
Section: Fig2 Effect Of Waste Addition On Water Of Consistency Of Csupporting
confidence: 83%
“…This was due to the fact that LSP are relatively soft and not strong enough to resist the pressure resulting from the denser microstructure resulting in crushing of microbes. Sand, being harder and coarser as compared to LSP, provides better cover in the denser microstructure as previously reported by Thongsanitgarn et al (2012).…”
Section: Compressive Strength Regainsupporting
confidence: 72%
“…The effects of limestone have been observed to alter aspects of the cement performance through the proposed mechanisms of dilution, the filler effect (particle packing), and nucleation (4,6,(17)(18)(19)(20)(21)(22)(23). Many authors have observed that these mechanisms affect the hydration of the cement, subsequently modifying the performance of the overall system (4,6,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). It is important to note that these mechanisms are interrelated and act simultaneously, influencing many of the same parameters of the system.…”
Section: Mechanisms Associated With Limestone Replacements In Cementmentioning
confidence: 99%